Analisis Perputaran Piutang Pasien BPJS Ketenagakerjaan pada Rumah Sakit XY di Surabaya (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the accounts receivable turnover for BPJS Employment patients at a XY  hospital in Surabaya. Efficient management of receivables is crucial in maintaining liquidity and the financial health of the hospital, as well as supporting the delivery of quality services. Data were collected through interviews, documentation, and purposive sampling of the hospital's finance head. The results indicate that the duration of converting receivables into cash and delays in payment accordance with the due date are primary factors influencing the BPJS Employment accounts receivable turnover. Additionally, complete administrative documentation and a rapid verification process play important roles in accelerating claim disbursement. This study recommends improvements in administrative management and collection strategies to optimize receivable turnover, thereby enhancing financial efficiency and service quality at the private hospital.
Keywords: Receivable Turnover, BPJS Employment, RS XY